Development of a New Method for Synthesizing HITEC Salt-Based Alumina Nanofluids - Marllory Isaza Ruiz; Francisco Javier Bolivar Osorio (Ingeniería e Investigación, 2022)
This study presents a new two-step method to synthesize molten salt-based nanofluids by replacing water with butanol and using an Emax high-energy mill to ensure good stability and homogeneity. Commercial HITEC molten salt was selected as the base fluid, and alumina nanoparticles (nominal size of 5,1 nm) were used as an additive in three different proportions: 0,5, 1,0, and 1,5 wt.%. The specific heat capacity was evaluated through two different methods: differential scanning calorimetry (DSC) and modulated differential scanning calorimetry (MDSC). According to the evaluation by MDSC, an increment of up to 4,27% in the specific heat capacity was achieved with 1,0 wt.% of alumina nanoparticles in comparison with the raw salt, without affecting the melting point and thermal stability of the salt. This behavior may be related to the good distribution of the nanoparticles in the salt. However, no significant improvement in the specific heat capacity of the nanofluid was observed when the standard DSC method was applied. This behavior may be due to the different sensitivities of the two methods to small changes in the sample, with MDSC being the more sensitive technique, as it establishes the contribution of the two phases that make up the nanofluid: the molten salt as the base fluid and the solid nanoparticles. Similarly, the heating rate used in each of the techniques can influence the sensitivity with regard to determining changes in nanofluids.